Non‐Doped Sky‐Blue OLEDs Based on Simple Structured AIE Emitters with High Efficiencies at Low Driven Voltages1. Issue 17 (4th August 2017) - Islam, Amjad; Zhang, Dongdong; Peng, Ruixiang; Yang, Rongjuan; Hong, Ling; Song, Wei; Wei, Qiang; Duan, Lian; Ge, Ziyi
Abstract: Blue organic light‐emitting diodes (OLEDs) are necessary for flat‐panel display technologies and lighting applications. To make more energy‐saving, low‐cost and long‐lasting OLEDs, efficient materials as well as simple structured devices are in high demand. However, a very limited number of blue OLEDs achieving high stability and color purity have been reported. Herein, three new sky‐blue emitters, 1, 4, 5‐triphenyl‐2‐(4‐(1, 2, 2‐triphenylvinyl)phenyl)‐1H‐imidazole (TPEI), 1‐(4‐methoxyphenyl)‐4, 5‐diphenyl‐2‐(4‐(1, 2, 2‐triphenylvinyl)phenyl)‐1H‐imidazole (TPEMeOPhI) and 1‐phenyl‐2, 4, 5‐tris(4‐(1, 2, 2‐triphenylvinyl)phenyl)‐1H‐imidazole (3TPEI), with a combination of imidazole and tetraphenylethene groups, have been developed. High photoluminescence quantum yields are obtained for these materials. All derivatives have demonstrated aggregation‐induced emission (AIE) behavior, excellent thermal stability with high decomposition and glass transition temperatures. Non‐doped sky‐blue OLEDs with simple structure have been fabricated employing these materials as emitters and realized high efficiencies of 2.41 % (4.92 cd A −1, 2.70 lm W −1 ), 2.16 (4.33 cd A −1, 2.59 lm W −1 ) and 3.13 % (6.97 cd A −1, 4.74 lm W −1 ) for TPEI, TPEMeOPhI and 3TPEI, with small efficiency roll‐off. These are among excellent results for molecules constructed from the combination of imidazole and TPE reported so far. The high performance of a 3TPEI‐based device shows the promising potential of the combination of imidazole and AIEgen for synthesizing efficient electroluminescent materials for OLED devices. Abstract : Blue skies smiling at me : Three novel imidazole‐based derivatives have been developed for OLED devices. Non‐doped sky‐blue OLEDs with simple structure have been fabricated employing these materials as emitters, and they show an excellent performance in comparison with other non‐doped devices with similar materials reported so far.